(untitled) (Journal of the College of Basic Education, 2022)
The art of slogan represented the innovative side in the designing process, on which to what extent this factor depends carried out by the company that designed the slogan for being regarded as the owner of the innovation. the art of slogan works in the core of the event and the slogan is a creative expression about new thoughts ; besides , the ability of creating new thoughts and ideas have been considered the main basic element for succeeding the message of active design depended on the skill of the idea creation, style , along with the method of processing it. This could lead to carry out the communicative goals of the slogan. The current research aims to: Uncovering the indications of the symbol in slogans of the mobile Specifying indication and symbols in slogans of mobile company. Communicating to know the basic elements that being depended on to design indication and symbols of the mobile company . The researcher has followed method of analyzing the content; the researcher has reached to the results as to achieve the research ’s goals. The researcher has chosen 5 slogans represented Iraqna ( Zain) - Asia Cell – Korek – Kilimat) ; the researcher has used the method of examining the samples to be analyzed depending on the forms prepared for this purpose. Most important results are: Details ,decoration and decorative Fonts interfered in the slogan lead to disperse its active performance ; besides deteriorating the vitality of the designing unity for each of space , and other units. Moreover, the missing of its partial parts related each to other. It has been appeared composite relationship accomplishment, to achieve the vitality of designing unity that in return accomplish the plastic elements